Assessment of Anisotropy in Cold In-Place Recycled Materials Using Shear Wave Velocity and Computed Tomography Analysis - Quentin Lecuru; Yannic Ethier; Alan Carter; Mourad Karray (Infrastructures)
Pavement materials like hot mix asphalt (HMA) and cold recycled mixes (CRMs) are typically considered isotropic. This study evaluates the anisotropy of a cold in-place recycled (CIR) material using the shear wave velocity (Vs) parameter. The piezoelectric ring actuator technique (P-RAT) is utilized to assess the Vs parameter in three directions in CIR slabs. Similarly, the ultrasonic pulse velocity (UPV) technique is employed to measure P-wave velocities. Both methods evaluate mechanical properties in multiple directions. Complex modulus tests are conducted to link velocities results to |E*| modulus. Finally, computed tomography (CT) scans are performed on the specimens in order to evaluate anisotropy resulting from aggregate alignment. The Vs obtained using P-RAT and the Vp from UPV indicate anisotropy, as the wave velocities differ across the three directions. Differences range from 0.6 to 11.6% in Vs, influenced by measurement location. UPV results are analysed in relation to the |E*| modulus master curves, demonstrating that the first peak arrival time for the P-wave corresponds with the master curve. CT scan analysis reveals that the aggregates tend to be more aligned in the direction of the compacting wheel’s displacement, which also highlights anisotropy.